2002
DOI: 10.1051/animres:2002001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low dietary starch/fibre ratio around weaning on intake behaviour, performance and health status of young and rabbit does

Abstract: -The influence of a low starch/fibre ratio (S/F) diet given to rabbits and does around weaning on their performance and health status was studied. In the LS group (n = 29 litters), the rabbits were fed a low S/F (0.68) diet (LS diet: 11.7 DE MJ·kg -1 DM) from day 18 to day 44; then they were changed to a fattening diet (F diet: 12.5 DE MJ·kg -1 DM). In the HS group (n = 29 litters), the rabbits were fed a high S/F (0.98) diet (HS diet: 12.6 DE MJ·kg -1 DM) from days 18 to 32 (weaning), and after weaning they r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
2

Year Published

2005
2005
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 16 publications
5
18
0
2
Order By: Relevance
“…A similar result was obtained by Gidenne and Perez [12] and by Maertens [20], and it might be attributed to a weak appetency possibly because of the very small particle size provided by the extrusion process. It should not be due to the digestible energy content of this diet, since in the young rabbit the feed intake is not dependent on the dietary digestible energy level [10].…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was obtained by Gidenne and Perez [12] and by Maertens [20], and it might be attributed to a weak appetency possibly because of the very small particle size provided by the extrusion process. It should not be due to the digestible energy content of this diet, since in the young rabbit the feed intake is not dependent on the dietary digestible energy level [10].…”
Section: Discussionmentioning
confidence: 99%
“…The DgF fraction plays a key role in digestive efficiency and digestive health, as it is rapidly fermented (compared with Mortality after weaning % Dietary ADF concentration, % as fed Gidenne et al, 2004bGidenne et al, 2004aDebray et al, 2002Bennegadi et al, 2001Perez et al, 1996Perez et al, 1994Perez et al, 1994Blas et al, 1994Carraro et al, 2007 Tazzoli 2012 CP15 Tazzoli 2012CP17 De Blas et al, 1981Maître et al, 1990 Figure 4 The rabbit post-weaning mortality decreases when the dietary lignocellulose (ADF) concentration increases, but with a highly variable impact within the classical dietary ADF range (15% to 22%). Data from 12 studies and 46 diets, without antibiotics, and varying in their ADF concentration.…”
Section: Brief Overview Of Polymers Of the Plant Cell Wall: Definitiomentioning
confidence: 99%
“…The HRi is improved, whereas the feed efficiency is weakly modified Gidenne et al, 2004b;Tazzoli et al, 2009;Trocino et al, 2011). Furthermore, a substitution of protein by DgF Health Risk index, after weaning % Ratio DgF /ADF in the feeds Gidenne et al, 2004bGidenne et al, 2004aDebray et al, 2002Bennegadi et al, 2001 lower HRi higher HRi Figure 7 The health risk index (HRi) of the growing rabbit depends on the balance between low-digested (ADF) and highly digested (DgF) fibre fractions. Data from five studies and 16 diets, without antibiotics, varying in their ratio DgF/ADF (within a study dietary ADF is varying).…”
Section: Brief Overview Of Polymers Of the Plant Cell Wall: Definitiomentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, other studies suggested that the regulation of the solid feed intake in young rabbits would implicate other mechanisms than the level of the digestible energy. Thus, young rabbits fed a 'high energy/ high starch' diet ingested more solid feed, with an equivalent amount of milk ingestion (Fortun-Lamothe et al, 2001) or furthermore with a higher milk intake (Debray et al, 2002;Gidenne et al, 2007). In our study, weaned rabbits ate 20% less digestible protein than suckling rabbits between 23 and 27 days of age.…”
Section: Discussionmentioning
confidence: 58%